Implementation of Value Added Tax in Nepal (Patan Pragya, 2021)
In the empirical study, the analysis has been done about VAT on the basis of information collected from experts, tax officials, businessmen and consumers. The tool basically used is questionnaire. The questions were asked to 60 different individuals related to this field. Empirical as well as theoretical analysis showed that VAT is superior to other types of Sales tax. Not only that, most of the respondents have also viewed in VAT as best instrument for research mobilization, bright future and discouraging illegal business. Similarly, most of the respondents (Tax Experts & Officials), argued that billing problem, open boarder, administrative incapability as hunting problem. They also discussed about legal provisions, choice between single or multi rated VAT, behavior of tax personnel, rate of VAT, need of public awareness programs etc.